PENGARUH PROFITABILITAS, PERTUMBUHAN PENJUALAN, KEPEMILIKAN INSTITUSIONAL DAN RISIKO BISNIS TERHADAP KEBIJAKAN PENDANAAN PERUSAHAAN RETAIL - FIRDAUS, MUTIA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: This study was conducted to examine and analyze the effect of profitability, sales growth, institutional ownership and business risk to the company’s retail financing policy in Indonesia Stock Exchange (BEI) in 2007-2012. The population used is a retail company that is listed on the Indonesia Stock Exchange (IDX), with a total of 15 companies. The analysis used is multiple regression analysis. Based on the research that has been done can be seen that based on the results of the simultaneous test is known that there is a significant effect of the variable profitability, sales growth, institutional ownership and business risk are jointly funding the policy. Only partially profitability variable which have a significant effect on the dependent variable funding policy. As for the sales growth variable, institutional ownership and business risk partially no significant effect on the dependent variable funding policy. Keywords: profitability, sales growth, institutional ownership, business risk and financing policy.